2011
DOI: 10.1007/s11367-011-0350-2
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of construction and demolition waste management systems: a Spanish case study

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 19 publications
4
40
0
2
Order By: Relevance
“…As concluded by Mercante et al (2012), the recycling of wood is not self-evidently beneficial for the environment. As a whole, the overall performance of the C&DW management system could be significantly improved by developing environmentally and economically beneficial recycling for the wood and mineral fractions and developing source separation and recycling of the miscellaneous and mixed waste.…”
Section: Possibilities To Improve the Performance Of The Canddw Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…As concluded by Mercante et al (2012), the recycling of wood is not self-evidently beneficial for the environment. As a whole, the overall performance of the C&DW management system could be significantly improved by developing environmentally and economically beneficial recycling for the wood and mineral fractions and developing source separation and recycling of the miscellaneous and mixed waste.…”
Section: Possibilities To Improve the Performance Of The Canddw Systemmentioning
confidence: 98%
“…Coelho and de Brito (2013) assessed a Portuguese C&DW recycling facility, and concluded that energy consumption and greenhouse gas emissions prevented through material recycling could be up to one order of magnitude greater than those generated. According to Mercante et al (2012), environmental impact savings are due to the recycling of plastics, metals, aggregates and wood for all the impact assessment categories assessed, except global warming in the case of wood and cardboard.…”
Section: Environmental and Economic Performance Of The Systemmentioning
confidence: 99%
“…Most of the studies focused on describing models for the design stage to estimate the volume of C&D waste that will be generated on a site (Mañà et al, 2000;Solís-Guzman et al, 2009;Martínez et al, 2010;Llatas, 2011;Marrero et al, 2011;de Guzmán et al, 2012;Villoria et al 2012). In other initiatives, such as those led by Ortiz et al (2010) and Mercante et al (2012), the research was based on life cycle assessment. Rodríguez et al (2007) analysed how environmental management systems contribute to the generation and management of C&D waste.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely known measures is the ''CW management hierarchy'', which refers to reduction, reuse, recycling and disposal [9]. Yet, this order of priorities does not ensure the minimization of environmental impacts of waste management systems or the optimal combination possible [10]. To address this issue, some applications of the life cycle assessment (LCA) methodology to C&D waste management have been reported in the literature [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%